Peru : Staff Report for the 2004 Article IV Consultation, Fourth Review Under the Stand-By Arrangement, and Request for Waiver of Nonobservance of Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper examines Peru's 2004 Article IV Consultation, Fourth Review Under the Stand-By Arrangement, and Request for Waiver of Nonobservance of Performance Criterion. In 2003, Peru's real GDP grew by 4 percent, with inflation of 2.5 percent and a further strengthening of the external position. Fiscal reforms have progressed well over the last two years, including the creation of a sound legal framework for fiscal decentralization, improved fiscal transparency, and further pension reforms. The authorities' economic program for 2004 foresees continued economic growth, based on a further recovery of investment and strong export growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet